The Reception of English Divorce Law in Malaysia: Or the Misadventures of What is Now Section 47 of Act 164 - Hickling, R.H. (Journal of Malaysian and Comparative Law, 2019)
Jurisdiction in matters of divorce came late to English courts. Not until the Divorce and Matrimonial Causes Act 1867 established the Court for Divorce and Matrimonial Causes could the courts order the dissolution of a marriage. Before the Act of 1857, to obtain a divorce (in the modern sense of the word) required a divorce a mensa et thoro, from bed and board, technically a separation, from the ecclesiastical courts, and divorce a vin-culo matrimonii from the bonds of marriage, by an Act of Parliament. Students of family law and addicts of Meggary will remember the ironic remarks of Maule J., which contributed to the legislation of 1857. Until that time, the law was unsatisfactory indeed.